TNFA gene in Brazilian patients with hemorrhagic stroke or cerebral aneurysm - Felipe S. A. Borges; Renata S. Freitas; Rafael M. Morais; Silvana S. Funghetto; Otávio T. Nóbrega; Luzitano B. Ferreira; Daniel O. Freire; Hélia Carla Souza; Izabel Cristina R. Silva (Sociedade Brasileira de Patologia Clínica, 2018)
ABSTRACT Introduction: Many cerebrovascular diseases display a relation with inflammatory processes. Furthermore, the influence of several polymorphisms has been studied to improve the knowledge of physiological mechanisms of the nervous system. Objectives: The aim of this study was to identify if there was an association between a polymorphism in -308 position of the TNFA gene and the development of hemorrhagic stroke or aneurysm in Distrito Federal, Brazil. Methods: We collected the clinical information and the medical records from hemorrhagic stroke or aneurysm patients. The occurrence of stroke or aneurysm was confirmed by computed tomography (CT) or magnetic resonance image (MRI). The TNFA genotypes were determined by polymerase chain reaction restriction fragment length polymorphism. Results: The AG genotype appears to decrease the occurrence of hemorrhagic stroke or aneurysm in people between 45-63 years. Our study was the first to investigate this association in a Brazilian sample, although a previous report showed a similar effect with ischemic stroke in a Chinese population. Conclusion: The TNFA -308 AG genotype is associated with a decreased risk of aneurysm or hemorrhagic stroke in a population from the capital of Brazil, Distrito Federal.